2017
DOI: 10.1016/j.ejpb.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin/poly(2-methyl-2-oxazoline-b-tetrahydrofuran-b-2-methyl-2-oxazoline) formulation: An improved penetration and biological effect of curcumin in F508del-CFTR cell lines

Abstract: Neutral amphiphilic triblock ABA copolymers are of great interest to solubilize hydrophobic drugs. We reported that a triblock ABA copolymer consisting of methyl-2-oxazoline (MeOx) and tetrahydrofuran (THF) (MeOx-THF-MeOx) (TBCP2) can solubilize curcumin (Cur) a very hydrophobic molecule exhibiting multiple therapeutic effects but whose insolubility and low stability in water is a major drawback for clinical applications. Here, we provide evidences by flow cytometry and confocal microscopy that Cur penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Their apoptotic, autophagic, anti-inflammatory effects and maintaining redox balance make them promising anti breast cancer agents (Losada-Echeberria et al 2017). Curcumin, genistein, quercetin, resveratrol and silibinin are reported to have great potential against breast cancer (Goncalves et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Their apoptotic, autophagic, anti-inflammatory effects and maintaining redox balance make them promising anti breast cancer agents (Losada-Echeberria et al 2017). Curcumin, genistein, quercetin, resveratrol and silibinin are reported to have great potential against breast cancer (Goncalves et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It can be interpreted that an increase in the chroma values indicates the conversion of curcumin from its keto to enol form. Yet, a less positive value was observed for the 0.1% TP at 5% SB (Figure d–f); the concentration of curcumin at a high level of SB increases the darkness of the sample and gives a higher redness value …”
Section: Results and Discussionmentioning
confidence: 91%
“…Still on this note, the very hydrophobic nature and low stability in water of compounds, such as curcumin, is a major drawback in their clinical application. In a very recent work, Gonçalves et al 69 showed that the neutral amphiphilic triblock copolymer MeOx6-THF19-MeOx6 (TBCP2) can solubilize curcumin and facilitate its penetration in Phe508del CFTR human airway epithelial cells, enhancing curcumin potentiation of CFTR mediate Cl-selective currents in these cells. These data suggests that TBCP2 may constitute a helpful tool for the delivery of this and other highly insoluble therapeutic drugs to CF patients.…”
Section: Aonmentioning
confidence: 99%